2009
DOI: 10.1590/s0100-69162009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Produção de mudas de mamoeiro utilizando diferentes substratos, ambientes de cultivo e recipientes

Abstract: No Estado de Mato Grosso do Sul, a fruticultura é limitada de informações consistentes, referentes ao potencial de produção de mudas para exploração a campo. Este trabalho avaliou a produção de biomassa em mudas de mamoeiro em diferentes ambientes de cultivo, recipientes e substratos na Universidade Estadual de Mato Grosso do Sul, Aquidauana - MS, de setembro a novembro de 2006. Utilizaram-se os ambientes de cultivo: estufa com filme de polietileno de baixa densidade; viveiro com tela de monofilamento preta; v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
5
8
1
5
Order By: Relevance
“…The greater availability of nutrients, due to higher volume, resulted in higher dry weight accumulation through the accumulation of carbohydrates, minerals, proteins, fibers and lipids in papaya seedlings. For papaya, this result of higher volume of the container is in agreement with the results obtained by MENDONÇA et al (2003), ARAÚJO et al (2006), COSTA et al (2009a) and COSTA et al (2010a. The period was more favorable to the development of seedlings in the greenhouse and Aluminet ® (Table 3) as they promote better conservation of thermal energy, since the average temperature was 22.0 °C.…”
Section: Resultssupporting
confidence: 92%
“…The greater availability of nutrients, due to higher volume, resulted in higher dry weight accumulation through the accumulation of carbohydrates, minerals, proteins, fibers and lipids in papaya seedlings. For papaya, this result of higher volume of the container is in agreement with the results obtained by MENDONÇA et al (2003), ARAÚJO et al (2006), COSTA et al (2009a) and COSTA et al (2010a. The period was more favorable to the development of seedlings in the greenhouse and Aluminet ® (Table 3) as they promote better conservation of thermal energy, since the average temperature was 22.0 °C.…”
Section: Resultssupporting
confidence: 92%
“…Both vermiculite, which had already showed better results for other fruit (COSTA et al, 2009;COSTA et al, 2010 c), and the substrates containing 100% cattle manure or 33.33%, promoted best physical structure to the substrates (aeration, moisture retention and porosity) and facilitated nutrient absorption by baruzeiro seedlings. DIAS et al (2009) found that the use of manure above 10% in substrate reduced root development and leaf expansion of mangaba seedlings cultivated in a greenhouse, different from what was observed in the present study.…”
Section: Resultsmentioning
confidence: 87%
“…Aliado e interagindo com os substratos, o ambiente de cultivo protegido influência o desenvolvimento inicial da planta (Costa et al, 2009), agregando vigor às mudas e, consequentemente, melhor adaptação e pegamento a campo (Costa et al, 2011). Para Zanella et al (2006), a utilização de sombreamento é uma importante técnica na formação de mudas frutíferas, pois afeta diretamente o crescimento da planta e posteriormente a formação do pomar.…”
Section: Introdução E Objetivosunclassified